Decision Determining Factors of Planting for Sustainable Agriculture - Kurniati, Evi (Fakultas Teknologi Pertanian Universitas Brawijaya, 2005)
Various factors need to consider in running an agriculture system sustainable.Â The objective of the study was to determine the most important factor on the farming decision making to run a sustainable agriculture system. Descriptive and inferential analytic methods were chosen as the research methodology. The data collected includes several variables covering economical, ecological, human resources and social aspect. A questionnaire was used as a tool to collect the prime data, and then followed by an evaluation of the multiple regressions in order to know the relationship level amongst economy, ecology, human resource and social variable to farming decision making. The result shows that the relationship amongst the variables may be expressed in a linear mathematical model as follows: Farming Dec. Making = - 0.585 + 1.01 Economy + 1.08 Ecology + 0.969 HR + 1.02 Social. The equation model indicates that the ecological variable is to be the most dominant factor in running a sustainable agriculture. Therefore, such variables must be defined to ensure that the agriculture system is run sustainable. Â Key Words: farming decision making, sustainable agriculture